Case study: design and implementation of training for scientists deploying to Ebola diagnostic field laboratories in Sierra Leone: October 2014 to February 2016. (26th May 2017) - Logue, Christopher H.; Lewis, Suzanna M.; Lansley, Amber; Fraser, Sara; Shieber, Clare; Shah, Sonal; Semper, Amanda; Bailey, Daniel; Busuttil, Jason; Evans, Liz; Carroll, Miles W.; Silman, Nigel J.; et al.
Abstract : As part of the UK response to the 2013–2016 Ebola virus disease (EVD) epidemic in West Africa, Public Health England (PHE) were tasked with establishing three field Ebola virus (EBOV) diagnostic laboratories in Sierra Leone by the UK Department for International Development (DFID). These provided diagnostic support to the Ebola Treatment Centre (ETC) facilities located in Kerry Town, Makeni and Port Loko. The Novel and Dangerous Pathogens (NADP) Training group at PHE, Porton Down, designed and implemented a pre-deployment Ebola diagnostic laboratory training programme for UK volunteer scientists being deployed to the PHE EVD laboratories. Here, we describe the training, workflow and capabilities of these field laboratories for use in response to disease epidemics and in epidemiological surveillance. We discuss the training outcomes, the laboratory outputs, lessons learned and the legacy value of the support provided. We hope this information will assist in the recruitment and training of staff for future responses and in the design and implementation of rapid deployment diagnostic field laboratories for future outbreaks of high consequence pathogens. This article is part of the themed issue 'The 2013–2016 West African Ebola epidemic: data, decision-making and disease control'.